High-strength fly ash-based geopolymer glue slurry and preparation method thereof

By activating fly ash and slag and introducing nanosilicon dioxide and hydrophilic groups on the surface of the polyester fiber, the compressive and flexural strength of the fly ash base polymer glue slurry is improved, and its lower strength is solved The problem.

CN119461959AActive Publication Date: 2025-02-18TONGJI UNIV +1

Patent Information

Application Number
CN202411463663.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

Fly ash base polymer glue slurry has low flexural resistance and compressive strength.

Method used

Using the composite ratio of activated geopolymer precursor, alkali trigger, aggregate, silica grafted polyester fiber and water, fly ash and slag are activated by ball milling, and nanosilicon dioxide is introduced on the surface of the modified polyester fiber. and hydrophilic groups to improve the compatibility of fibers with geopolymer precursors.

Benefits of technology

The compressive strength and flexural strength of the fly ash base polymer glue slurry are significantly improved, meeting the high-strength needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092660210000081
    Figure BDA0005092660210000081
Patent Text Reader

Abstract

The invention relates to the technical field of geopolymers, and discloses a high-strength fly ash-based geopolymer glue slurry and a preparation method thereof, the high-strength fly ash-based geopolymer glue slurry comprises 62-70 parts by weight of an activated geopolymer precursor, 7-11 parts by weight of an alkali activator, 80-95 parts by weight of aggregate, 0.4-2 parts by weight of silica grafted polyester fiber, and 18-22 parts by weight of water. The preparation method comprises the following steps: carrying out ball-milling activation on fly ash and slag by using triethanolamine to obtain an activated geopolymer precursor; the surface of the polyester fiber is grafted with nano silicon dioxide, the nano silicon dioxide has a good interface compatilizer with a silicon dioxide phase and a silicate phase in the fly ash and the slag, the compatibility between the polyester fiber and a geopolymer precursor is improved, meanwhile, hydrophilic groups such as carboxyl and imino are introduced to the surface of the fiber, the dispersity in water-based slurry is better, and under the synergistic effect, the water-based slurry is better in water-based property. The compressive strength and the breaking strength of the geopolymer glue slurry test piece are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geopolymers, in particular to a high-strength fly ash-based polymer mortar and a preparation method thereof. Background Art

[0002] Geopolymer is an inorganic polymer with a tetrahedral three-dimensional network structure formed by a chemical reaction between a precursor and an activator. The precursors are mainly industrial solid wastes such as slag, steel slag, silica fume, fly ash, and red mud, and the activators are alkali metal hydroxides, carbonates, phosphates, etc. Geopolymer materials have good mechanical and durability properties and can effectively replace traditional cement. At the same time, they can absorb a large amount of industrial solid waste, which is of great significance to promoting the transportation industry to reduce carbon emissions and save costs throughout the life cycle. Geopolymers are gradually being valued as a low-carbon, green cementitious material. With appropriate materials and proportions, geopolymers can show better mechanical properties than silicate cement. Compared with traditional cement-based cementitious materials, the composition of geopolymer cementitious materials is more complex, and the performance of the system composed of different precursors and alkali activators is quite different. Therefore, selecting an appropriate geopolymer cementitious material system and focusing on the proportion and performance of geopolymer mortar are the prerequisites for preparing permeable geopolymer concrete with excellent performance, low carbon and environmental protection.

[0003] Polyester fiber is a chemical synthetic fiber with high mechanical strength, good chemical stability, strong high and low temperature resistance, and is widely used in building materials such as cement, asphalt, and concrete. Patent CN113026360B discloses that polyester fiber is subjected to alkaline hydrolysis to obtain hydrolyzed polyester fiber; then an acidic crosslinking agent and polyvinyl alcohol are cured on the hydrolyzed polyester fiber to form a submicron or micron thick coating, and the obtained modified polyester fiber can be used in engineering cement-based composite materials. However, the modified polyester fiber does not improve the compressive and flexural strength of cement materials. Summary of the invention

[0004] The invention solves the problem that the flexural and compressive strengths of fly ash-based polymer mortar are low.

[0005] The technical solution provided by the present invention is: a high-strength fly ash-based polymer mortar, characterized in that it includes 62-70 parts by weight of activated geopolymer precursor, 7-11 parts by weight of alkali activator, 80-95 parts by weight of aggregate, 0.4-2 parts by weight of silica-grafted polyester fiber, and 18-22 parts by weight of water.

[0006] The preparation method of the activated geopolymer precursor is as follows: fly ash, slag and grinding aid triethanolamine are added into a ball mill for ball milling, and the material is discharged to obtain the activated geopolymer precursor.

[0007] The preparation method of silica grafted polyester fiber is as follows: add serine grafted polyester fiber to N,N-dimethylformamide, heat to 50-60°C, stir for 2-3h, then add toluene diisocyanate modified nano silica and dibutyltin dilaurate, heat to 80-90°C, react for 12-24h, filter, wash with ethanol, and dry to obtain silica grafted polyester fiber.

[0008] Preferably, the alkali activator is water glass with a modulus of 1.4-1.6; the aggregate is basalt with an average particle size of 4.75-9.5 mm.

[0009] Preferably, the slag is alkaline slag, and the slag includes the following components in mass fractions: 38.55% CaO, 11.69% Al2O3, 1.04% Fe2O3, 32.95% SiO2, and 9.11% MgO; the fly ash includes the following components in mass fractions: 10.4% CaO, 20.3% Al2O3, 5.30% Fe2O3, 55.0% SiO2, and 0.98% MgO.

[0010] Preferably, in the method for preparing the activated geopolymer precursor, the mass ratio of fly ash, slag and triethanolamine is (35-45):(55-65):(0.01-0.02).

[0011] Preferably, in the method for preparing the activated geopolymer precursor, the ball milling speed is 300-600 r / min, and the ball milling time is 45-90 min.

[0012] Preferably, in the preparation method of silica-grafted polyester fiber, the mass ratio of serine-grafted polyester fiber, toluene diisocyanate-modified nano-silica, and dibutyltin dilaurate is 100:(15-60):(0.12-0.5).

[0013] Preferably, the preparation method of serine grafted polyester fiber is:

[0014] (1) Add glycidyl methacrylate and benzoin ethyl ether to acetone, stir and dissolve to obtain a monomer solution, wherein the concentration of glycidyl methacrylate is controlled to be (0.6-1.8) mol / L, and the concentration of benzoin ethyl ether is controlled to be (0.05-0.15) mol / L; then add polyester fiber and soak for 2-3 hours, then irradiate the fiber under a 400-600 W high pressure mercury lamp to carry out ultraviolet grafting reaction for 10-20 minutes, wash with xylene, ethanol and water in turn, and dry to obtain GMA grafted polyester fiber.

[0015] (2) Add GMA grafted polyester fiber to N,N-dimethylformamide, heat to 50-60°C, stir for 2-3 hours, then add serine (8-36% by weight of the GMA grafted polyester fiber), stir and react for 12-18 hours, filter, wash with water and ethanol in turn, and dry to obtain serine grafted polyester fiber.

[0016] Preferably, the preparation method of high-strength fly ash-based polymer mortar is: add silica-grafted polyester fiber to water, disperse it by ultrasound, then add alkali activator, stir for 30-60s, and then continuously add activated polymer precursor, control the addition time to 120-180s, stir while adding, and finally add aggregate, stir for 60-120s, then pour the material into a mold, vibrate to degas, and cure to obtain high-strength fly ash-based polymer mortar.

[0017] The technical effect of the present invention is as follows: the present invention utilizes glycidyl methacrylate to perform ultraviolet grafting modification on polyester fibers, introduces epoxy groups on the surface of the polyester fibers, and then utilizes the amino groups of serine to react with the epoxy groups to obtain serine-grafted polyester fibers, thereby introducing active hydroxyl groups, as well as carboxyl and imino hydrophilic groups on the surface of the polyester fibers, and further the active hydroxyl groups react with the isocyanate groups of toluene diisocyanate-modified nano-silica, thereby modifying the nano-silica on the surface of the polyester fibers to obtain silica-grafted polyester fibers.

[0018] The present invention uses triethanolamine as a grinding aid to perform ball milling activation on fly ash and slag to obtain an activated geopolymer precursor. After ball milling activation with the triethanolamine grinding aid, the hindering effect of the double-layer glass protective layer rich in SiO2 and SiO2-Al2O3 in the fly ash and slag is reduced, and the internal soluble SiO2 and Al2O3 phases can be dissolved, thereby improving the chemistry of the geopolymer precursor. Silicon dioxide grafted polyester fiber is used as a fiber reinforcing agent and compounded with water, aggregate, and water glass activator to obtain a geopolymer mortar material specimen. The surface of the polyester fiber is grafted with nano-silicon dioxide, which not only has the advantages of high strength and high structural stability, but also has good interface compatibilizers with the silicon dioxide phase and silicate phase in the fly ash and slag, thereby improving the compatibility between the polyester fiber and the geopolymer precursor and playing a better reinforcing role. In addition, the polyester fiber surface is grafted and modified by serine, and hydrophilic groups such as carboxyl and imino groups are introduced into the fiber surface, which can improve the dispersibility of the fiber in the aqueous slurry and further enhance the reinforcing effect of the polyester fiber. Under the synergistic effect, the compressive strength and flexural strength of the geopolymer slurry specimens are improved. DETAILED DESCRIPTION

[0019] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0020] The slag in the embodiment of the present invention is alkaline slag, and the mass fraction of CaO in the slag is 38.55%, the mass fraction of Al2O3 is 11.69%, the mass fraction of Fe2O3 is 1.04%, the mass fraction of SiO2 is 32.95%, and the mass fraction of MgO is 9.11%.

[0021] The mass fraction of CaO in fly ash is 10.4%, the mass fraction of Al2O3 is 20.3%, the mass fraction of Fe2O3 is 5.30%, the mass fraction of SiO2 is 55.0%, and the mass fraction of MgO is 0.98%.

[0022] The preparation method of toluene diisocyanate modified nano-silica is as follows: add 2g of nano-silica (average particle size 30nm) and 2g of toluene-2,4-diisocyanate into 150mL of toluene, heat to 90°C, react for 12h, centrifuge, wash with toluene, and dry to obtain toluene diisocyanate modified nano-silica.

[0023] Example 1

[0024] (1) Add 180 mmol of glycidyl methacrylate and 15 mmol of benzoin ethyl ether to 100 mL of acetone, stir and dissolve to obtain a monomer solution, then add 8 g of polyester fiber and soak for 2 h. Then irradiate the fiber under a 400 W high-pressure mercury lamp to perform ultraviolet grafting reaction for 20 min, wash with xylene, ethanol and water in turn, and dry to obtain GMA-grafted polyester fiber.

[0025] (2) Add 5 g of GMA grafted polyester fiber to 300 mL of N,N-dimethylformamide, heat to 50°C, stir for 3 h, then add 1.8 g of serine, stir and react for 18 h, filter, wash with water and ethanol in turn, and dry to obtain serine grafted polyester fiber.

[0026] (3) Add 5 g of serine grafted polyester fiber to 400 mL of N,N-dimethylformamide, heat to 55 °C, stir for 3 h, then add 3 g of toluene diisocyanate-modified nano-silica and 25 mg of dibutyltin dilaurate, heat to 80 °C, react for 24 h, filter, wash with ethanol, and dry to obtain silica grafted polyester fiber.

[0027] (4) 35 g of fly ash, 65 g of slag, and 0.01 g of triethanolamine as a grinding aid were added into a ball mill and ball milled for 60 min at a speed of 500 r / min to obtain an activated geopolymer precursor.

[0028] (5) 4 g of silica-grafted polyester fiber was added to 180 g of water and dispersed by ultrasound. Then, 110 g of water glass with a modulus of 1.5 as an alkali activator was added and stirred for 60 seconds. Then, 650 g of activated geopolymer precursor was continuously added, and the addition time was controlled to be 120 seconds while stirring. Finally, 860 g of basalt aggregate with an average particle size of 9.5 mm was added and stirred for 120 seconds. Then, the material was poured into a mold, vibrated for degassing, and cured at 20° C. for 7-28 days with a relative humidity of 90% to obtain a high-strength fly ash-based polymer mortar.

[0029] Example 2

[0030] (1) Add 120 mmol of glycidyl methacrylate and 10 mmol of benzoin ethyl ether to 100 mL of acetone, stir and dissolve to obtain a monomer solution, then add 8 g of polyester fiber and soak for 3 h. Then irradiate the fiber under a 400 W high-pressure mercury lamp to perform ultraviolet grafting reaction for 20 min, wash with xylene, ethanol and water in turn, and dry to obtain GMA-grafted polyester fiber.

[0031] (2) Add 5 g of GMA grafted polyester fiber to 300 mL of N,N-dimethylformamide, heat to 50°C, stir for 2 h, then add 1.2 g of serine, stir and react for 12 h, filter, wash with water and ethanol in turn, and dry to obtain serine grafted polyester fiber.

[0032] (3) Add 5 g of serine-grafted polyester fiber to 350 ml of N,N-dimethylformamide, heat to 50 ° C, stir for 3 h, then add 1.8 g of toluene diisocyanate-modified nano-silica and 15 mg of dibutyltin dilaurate, heat to 80 ° C, react for 24 h, filter, wash with ethanol, and dry to obtain silica-grafted polyester fiber.

[0033] (4) 35 g of fly ash, 65 g of slag, and 0.015 g of triethanolamine as a grinding aid were added into a ball mill and ball milled for 60 min at a speed of 300 r / min to obtain an activated geopolymer precursor.

[0034] (5) Add 12 g of silica-grafted polyester fiber to 220 g of water and disperse it by ultrasound. Then add 70 g of water glass, an alkali activator with a modulus of 1.6, and stir for 30 seconds. Then, continuously add 700 g of activated geopolymer precursor, and control the addition time to 180 seconds while stirring. Finally, add 800 g of basalt aggregate with an average particle size of 9.5 mm and stir for 120 seconds. Then, pour the material into a mold, vibrate to degas, and cure at 20° C. for 7-28 days with a relative humidity of 90% to obtain a high-strength fly ash-based polymer mortar.

[0035] Example 3

[0036] (1) Add 60 mmol of glycidyl methacrylate and 5 mmol of benzoin ethyl ether to 100 mL of acetone, stir and dissolve to obtain a monomer solution, then add 8 g of polyester fiber and soak for 2 h. Then irradiate the fiber under a 600 W high-pressure mercury lamp to perform ultraviolet grafting reaction for 10 min, wash with xylene, ethanol and water in turn, and dry to obtain GMA-grafted polyester fiber.

[0037] (2) Add 5 g of GMA grafted polyester fiber to 200 mL of N,N-dimethylformamide, heat to 60°C, stir for 2 h, then add 0.4 g of serine, stir and react for 12 h, filter, wash with water and ethanol in turn, and dry to obtain serine grafted polyester fiber.

[0038] (3) Add 5 g of serine-grafted polyester fiber to 300 mL of N,N-dimethylformamide, heat to 60 ° C, stir for 2 h, then add 0.75 g of toluene diisocyanate-modified nano-silica and 6 mg of dibutyltin dilaurate, heat to 90 ° C, react for 12 h, filter, wash with ethanol, and dry to obtain silica-grafted polyester fiber.

[0039] (4) 40 g of fly ash, 60 g of slag, and 0.02 g of triethanolamine as a grinding aid were added into a ball mill and ball milled for 60 min at a speed of 600 r / min to obtain an activated geopolymer precursor.

[0040] (5) Add 20 g of silica-grafted polyester fiber to 220 g of water and disperse it by ultrasonic. Then add 95 g of water glass, an alkali activator with a modulus of 1.4, and stir for 60 seconds. Then, continuously add 620 g of activated geopolymer precursor, and control the addition time to 120 seconds while stirring. Finally, add 950 g of basalt aggregate with an average particle size of 4.75 mm and stir for 120 seconds. Then, pour the material into a mold, vibrate to degas, and cure at 20° C. for 7-28 days with a relative humidity of 90% to obtain a high-strength fly ash-based polymer mortar.

[0041] Comparative Example 1

[0042] (1) Silica-grafted polyester fibers were prepared according to the method of Example 1.

[0043] (2) Add 35 g of fly ash and 65 g of slag into a ball mill and mill for 60 min at a speed of 500 r / min to obtain a geopolymer precursor.

[0044] (3) 4 g of silica-grafted polyester fiber was added to 180 g of water and dispersed by ultrasound. Then, 110 g of water glass with a modulus of 1.5 as an alkali activator was added and stirred for 60 seconds. Then, 650 g of geopolymer precursor was continuously added and the addition time was controlled to be 120 seconds while stirring. Finally, 860 g of basalt aggregate with an average particle size of 9.5 mm was added and stirred for 120 seconds. Then, the material was poured into a mold, vibrated for degassing, and cured at 20° C. for 7-28 days with a relative humidity of 90% to obtain a high-strength fly ash-based polymer mortar.

[0045] Comparative Example 2

[0046] (1) Prepare an activated geopolymer precursor according to the method of Example 1.

[0047] (2) Add 110 g of alkali activator water glass with a modulus of 1.5 to 180 g of water, stir for 60 seconds, then continuously add 650 g of activated geopolymer precursor, control the addition time to 120 seconds, stir while adding, finally add 860 g of basalt aggregate with an average particle size of 9.5 mm, stir for 120 seconds, then pour the material into a mold, vibrate to degas, and cure at 20° C. for 7-28 days with a relative humidity of 90% to obtain a high-strength fly ash-based polymer mortar.

[0048] Comparative Example 3

[0049] (1) Prepare an activated geopolymer precursor according to the method of Example 1.

[0050] (2) 4 g of polyester fiber was added to 180 g of water and dispersed by ultrasound. Then, 110 g of water glass with a modulus of 1.5 as an alkali activator was added and stirred for 60 seconds. Then, 650 g of activated geopolymer precursor was continuously added and the addition time was controlled to be 120 seconds while stirring. Finally, 860 g of basalt aggregate with an average particle size of 9.5 mm was added and stirred for 120 seconds. Then, the material was poured into a mold, vibrated for degassing, and cured at 20° C. for 7-28 days with a relative humidity of 90% to obtain a high-strength fly ash-based polymer mortar.

[0051] Comparative Example 4

[0052] (1) Serine-grafted polyester fibers were prepared according to the method of Example 1.

[0053] (2) Prepare an activated geopolymer precursor according to the method of Example 1.

[0054] (3) 4 g of serine grafted polyester fiber was added to 180 g of water and dispersed by ultrasound. Then, 110 g of water glass with a modulus of 1.5 as an alkali activator was added and stirred for 60 seconds. Then, 650 g of activated geopolymer precursor was continuously added and the addition time was controlled to be 120 seconds while stirring. Finally, 860 g of basalt aggregate with an average particle size of 9.5 mm was added and stirred for 120 seconds. Then, the material was poured into a mold, degassed by vibration, and cured at 20° C. for 7-28 days with a relative humidity of 90% to obtain a high-strength fly ash-based polymer mortar.

[0055] The compressive strength and flexural strength of the mortar specimens are tested according to GB / T 17671-2021 standard.

[0056]

[0057] After testing, the fly ash-based polymer mortars of Examples 1-3 all showed good compressive strength and flexural strength. This is mainly because triethanolamine was used as a grinding aid to activate fly ash and slag by ball milling to obtain an activated geopolymer precursor. At the same time, silica-grafted polyester fibers were added, and nano-silicon dioxide was grafted on the surface of the polyester fibers. Nano-silicon dioxide not only has the advantages of high strength and high structural stability, but also has good interfacial compatibilizers with the silica phase and silicate phase in fly ash and slag, thereby improving the compatibility between the polyester fiber and the geopolymer precursor and playing a better reinforcing role. In addition, the grafting modification of the polyester fiber grafting surface with serine and the introduction of hydrophilic groups such as carboxyl and imino groups on the fiber surface can improve the dispersibility of the fiber in the aqueous slurry, further improve the reinforcing effect of the polyester fiber, and under the synergistic effect, improve the compressive strength and flexural strength of the geopolymer mortar specimens.

[0058] Compared with Example 1, Comparative Example 1 did not use triethanolamine to activate fly ash and slag by ball milling, so the activity of the obtained geopolymer precursor was lower, and the compressive strength and flexural strength of the mortar specimen were lower than those in Example 1.

[0059] In Comparative Example 2, no silica-grafted polyester fiber was added, and the compressive strength and flexural strength of the mortar specimen were significantly lower than those in Example 1.

[0060] In Comparative Example 3, ordinary unmodified polyester fiber is added, which does not contain nano-silica on its surface, has poor compatibility with the geopolymer precursor formed by fly ash and slag, and does not contain hydrophilic groups such as carboxyl and imino groups on its surface. It has poor dispersibility in the aqueous slurry, and has poor reinforcing effect on the slurry specimens, resulting in lower compressive strength and flexural strength than Example 1.

[0061] The surface of the serine-grafted polyester fiber added in Comparative Example 4 does not contain nano-silica, has poor compatibility with the geopolymer precursor, and has a poor reinforcing effect, resulting in lower compressive strength and flexural strength than Example 1.

[0062] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high-strength fly ash-based polymer mortar, characterized in that: The geopolymer mortar comprises 62-70 parts by weight of an activated geopolymer precursor, 7-11 parts by weight of an alkali activator, 80-95 parts by weight of an aggregate, 0.4-2 parts by weight of a silica-grafted polyester fiber, and 18-22 parts by weight of water; The preparation method of the activated geopolymer precursor comprises: adding fly ash, slag and triethanolamine as a grinding aid into a ball mill for ball milling, discharging the material, and obtaining the activated geopolymer precursor; The preparation method of the silica grafted polyester fiber is as follows: adding serine grafted polyester fiber to N,N-dimethylformamide, heating to 50-60°C, stirring for 2-3h, then adding toluene diisocyanate modified nano silica and dibutyltin dilaurate, heating to 80-90°C, reacting for 12-24h, filtering, washing, and drying to obtain the silica grafted polyester fiber.

2. The high-strength fly ash-based polymer mortar according to claim 1, characterized in that: The alkali activator is water glass with a modulus of 1.4-1.6; the aggregate is basalt with an average particle size of 4.75-9.5 mm.

3. The high-strength fly ash-based polymer mortar according to claim 1, characterized in that: The slag is alkaline slag, and the slag includes the following components in mass fractions: 38.55% of CaO, 11.69% of Al2O3, 1.04% of Fe2O3, 32.95% of SiO2, and 9.11% of MgO; the fly ash includes the following components in mass fractions: 10.4% of CaO, 20.3% of Al2O3, 5.30% of Fe2O3, 55.0% of SiO2, and 0.98% of MgO.

4. The high-strength fly ash-based polymer mortar according to claim 1, characterized in that: In the preparation method of the activated geopolymer precursor, the mass ratio of fly ash, slag and triethanolamine is (35-45):(55-65):(0.01-0.02).

5. The high-strength fly ash-based polymer mortar according to claim 1, characterized in that: In the preparation method of the activated geopolymer precursor, the ball milling speed is 300-600 r / min, and the ball milling time is 45-90 min.

6. The high-strength fly ash-based polymer mortar according to claim 1, characterized in that: In the preparation method of the silica-grafted polyester fiber, the mass ratio of the serine-grafted polyester fiber, the toluene diisocyanate-modified nano-silica, and the dibutyltin dilaurate is 100:(15-60):(0.12-0.5).

7. The high-strength fly ash-based polymer mortar according to claim 6, characterized in that: The preparation method of the serine grafted polyester fiber is: (1) Add glycidyl methacrylate and benzoin ethyl ether to acetone, stir and dissolve to obtain a monomer solution, then add polyester fiber and soak for 2-3 hours, then irradiate the fiber under a 400-600W high-pressure mercury lamp to perform ultraviolet grafting reaction for 10-20 minutes, wash, and dry to obtain GMA-grafted polyester fiber; (2) Add GMA grafted polyester fiber to N,N-dimethylformamide, heat to 50-60°C, stir for 2-3 hours, then add serine, stir and react for 12-18 hours, filter, wash, and dry to obtain serine grafted polyester fiber.

8. The high-strength fly ash-based polymer mortar according to claim 6, characterized in that: In the above (1), the concentration of glycidyl methacrylate in the monomer solution is (0.6-1.8) mol / L, and the concentration of benzoin ethyl ether is (0.05-0.15) mol / L.

9. The high-strength fly ash-based polymer mortar according to claim 6, characterized in that: In the above (2), the mass ratio of GMA grafted polyester fiber to serine is 100:(8-36).

10. A method for preparing a high-strength fly ash-based polymer mortar according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: adding silica grafted polyester fiber into water, dispersing the fiber by ultrasonication, adding an alkali activator, stirring for 30-60 seconds, continuously adding an activated geopolymer precursor, controlling the adding time to be 120-180 seconds, stirring while adding, finally adding aggregate, stirring for 60-120 seconds, pouring the material into a mold, vibrating to degas, curing and molding, and obtaining a high-strength fly ash-based geopolymer mortar.

Citation Information

Patent Citations

  • Modified polyester fibers for cement-based composites and their surface modification methods

    CN113026360B

  • Porous material based on modified steel slag and preparation method of porous material

    CN107117940A

  • Preparation method of coal ash-based geopolymer with adjustable mechanical properties

    CN115716722A

  • Grafting modification method of basalt fiber

    CN117228974A

  • Regenerated composite fiber asphalt mixture and preparation method thereof

    CN117658529A

Cited By

  • Light and thin sweat-guiding quick-drying double-layer woven fabric with skin-core structure and preparation method and application of light and thin sweat-guiding quick-drying double-layer woven fabric

    CN119913653A

  • A lightweight sweat-conducting and quick-drying double-layer woven fabric with a skin-core structure, its preparation method and application

    CN119913653B